Health-related quality of life in polycystic ovary syndrome patients: A systematic review - Seyed Abdolvahab Taghavi; Fatemeh Bazarganipour; Ali Montazeri; Anoshirvan Kazemnejad; Reza Chaman; Ahmad Khosravi (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2015)
Background: Increasing attention to the concept of polycystic ovary syndrome (PCOS) health-related quality of life has led to the development of tool that aims to measure this concept. Objective: The purpose of this study was to conduct a systematic review of psychometric properties of the PCOS health-related quality of life questionnaire. Materials and Methods: A search of database (Pubmed, PsychInfo, CINAHL, CENTRAL, Scopus and SID) from January1998 to December 2013 yielded 6152 references of which 27 papers remained after review of the titles and abstracts. The reviewers used structural tools to analyze the articles, critically appraise papers, and extract the data. Finally, eight papers met the full inclusion criteria. Results: Studies suggested that the PCOS health-related quality of life questionnaire (PCOSQ)/or its modified version (MPCOSQ) have partial known groups validity. The convergent/divergent validity of the questionnaire also was found to be relatively acceptable. The PCOSQ/MPCOSQ reached acceptable benchmarks for its reliability coefficients. Regarding structural validity, some studies suggested that the PCOSQ/MPCOSQ have an extra dimension (related to menstruation) in addition to its existing dimensions for original or modified versions. Conclusion: The PCOSQ/MPCOSQ showed acceptable content and construct validity, reliability and internal consistency. However, some other properties, particularly those related to factor and longitudinal validity, absolute error of measurement, minimal clinically important difference and responsiveness still need to be evaluated.